Fasting, justification, and self-righteousness in Luke 18:9–14: A social-scientific interpretation as response to Friedrichson - Mathews, Steven H. (HTS teologiese studies, 2013)
This article provides a social-scientific interpretation of the role of fasting in Jesus’ parable of the Pharisee and the tax collector in Luke 18:9–14. Specifically, the article considers such social realia as honour and shame, collectivism, and purity in the interpretation of the text. The textual and social contexts of the text are considered. It is contended that in the parable Jesus presents a caricature of both the Pharisee and the tax collector to make a larger point, in which fasting is not a major consideration. The article also evaluates Friedrichson’s interpretation of this text, which depicts the Pharisee as fasting vicariously, resulting in the justification of the tax collector. Finally, the significance of this text in a holistic theology of fasting in the New Testament is considered.